Elemental analysis and hardness characterization of fermented green arabica coffee bean using Laser-Induced Breakdown Spectroscopy (LIBS) - Hartadi Beny Sulistyo; Ikhwani Rauzatul; Abdulmadjid Syahrun Nur (E3S Web of Conferences)
By applying fermentation, the value of Gayo Arabica coffee can increase nearly fourfold. This study aims to differentiate green bean coffee of ordinary (unfermented) and wine (fermented) types using Laser-Induced Breakdown Spectroscopy (LIBS). Visual distinction between the two is challenging, but LIBS enables element identification through spectral characteristics. Green bean samples were analyzed using LIBS under optimized conditions of 120 mJ laser energy and 1,000 ns delay time. Elements such as C, H, N, O, Ca, Mg, Na, K, W, and Rb were detected in both types. The spectral intensity of Ca was notably higher in ordinary coffee, with the Ca (II)/Ca (I) ratio 2.2 times that of fermented coffee, indicating a softer structure in fermented beans. This study demonstrates the potential of LIBS for distinguishing spectral characteristics of Gayo Arabica green beans.